APPLICATION OF CROSSWORD PUZZLE LEARNING MEDIA TO INCREASE STUDENTS' LEARNING INTEREST IN SOCIOLOGY LEARNING AT SMA MUHAMMADIYAH LAMAHALA - Tsaniyah Binti Zakaria (SocioEdu: Sociological Education, 2024)
The purpose of this study was to determine whether there was an increase in students' interest in learning in the application of crossword learning media in sociology learning at SMA Muhammadiyah Lamahala. The type of research used is a class action research. The research subjects were taken from class XII IIS 3 as many as 20 students. This research was conducted at Muhammadiyah Lamahala High School for the 2022/2023 academic year, which is located in East Adonara District, Lamahala Jaya Village. The data in this study are data obtained from tests and scores of interest in learning questionnaires. This research is motivated by the problem, namely the low interest in learning students in learning sociology. To overcome this problem, apply crossword puzzle media to increase students' learning interest. Based on the results of observations, the average percentage of students' learning interest indicators in the pre-cycle had not reached the KKM score percentage, which was 40% before the crossword puzzle media was applied. in cycle 1 has not reached the success criteria. The average percentage of students' learning interest indicators in cycle 1 is 65%. The average percentage of indicators of interest in learning has not yet reached the criteria for success in action because it has only reached 65%, so it is continued with cycle 2. Based on observations, the average percentage of indicators of interest in learning students in cycle 2 has reached the criteria for success. The average percentage of students' learning interest indicators in cycle 2 is 92.7%.